2022
DOI: 10.18295/squmj.8.2022.050
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Physicians’ Job Satisfaction

Abstract: Objectives: Physician satisfaction with their job can lead to a better quality of care, fewer chances of making errors, and better patient outcomes. The purpose of the study was to examine physician satisfaction; and to assess job satisfaction across several factors, such as quality of care, ease of practice, relationship with leadership, and inter-professional collaboration. Method: A descriptive cross-sectional design was used. Data were collected between July 2019 and January 2020. Participants provided dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…These studies underscore the paramount significance of positive inter-professional relationships as a critical driver of overall job satisfaction. [13][14][15] Compared to other aspects of physicians' job satisfaction, emotional exhaustion, and lower personal satisfaction also influenced predictors in both developed and developing countries.6 Like the outcomes of our current study, a study conducted at a tertiary care hospital in eastern India similarly discovered that doctors with postgraduate qualifications were less content compared to their colleagues with lower qualifications. 1 The working environment profoundly impacts job satisfaction.…”
Section: Discussionsupporting
confidence: 57%
“…These studies underscore the paramount significance of positive inter-professional relationships as a critical driver of overall job satisfaction. [13][14][15] Compared to other aspects of physicians' job satisfaction, emotional exhaustion, and lower personal satisfaction also influenced predictors in both developed and developing countries.6 Like the outcomes of our current study, a study conducted at a tertiary care hospital in eastern India similarly discovered that doctors with postgraduate qualifications were less content compared to their colleagues with lower qualifications. 1 The working environment profoundly impacts job satisfaction.…”
Section: Discussionsupporting
confidence: 57%
“…The same finding was reported from Pakistan: good pay will reduce stress [ 27 ]. In addition, a parallel study among physicians in Oman reported that lower income was the main reason for lack of satisfaction [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Good IPC enables early identi cation of problems, timely intervention, can prevent errors, improve patient safety and thus optimise the quality of patient care [27][28][29]. Moreover, collaborative relationships and leadership modalities were found to be determinants of job satisfaction among ICU staff [30][31][32]. A high level of job satisfaction among ICU staff, in turn, has shown to have a positive impact on patient care [33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%